Professional Autonomy in Medicine: Defending the Right of Conscience in Health Care beyond the Right to Religious Freedom - Rouse, Susan T. (Linacre Q, 2012)
Health-care professionals currently have the right to conscientiously object to any procedure that they deem as morally illicit or that, in their opinion, could harm the patient. However, the right of conscientious refusal in medicine is currently under severe scrutiny. Medical procedures such as abortion and physician-assisted suicide that are not commonly medically indicated, but that can be requested by the patient, represent a type of medical care that is the penultimate expression of patient autonomy. When a health-care provider exercises his or her conscience in a way that denies the patient immediate access to such procedures, many claim that patient autonomy has been oppressed by the religious convictions of the health-care professional. As such, there is a growing opposition to the protection of conscience rights in health care that deserves attention. A common strategy used to defend conscience rights has been to claim that under the United States Bill of Rights, the health-care professional must be allowed to exercise their religious liberties in the context of their profession. This rationale seems to ignite a more intense opposition to conscience rights as it seems to validate the sense that a health-care professional's religious convictions are protected at the cost of patient autonomy. This paper reviews the current status of this debate and proposes a defense of conscience rights in health care that considers both the autonomy of the health-care worker and that of the patient in the context of the patient-physician relationship.